An enhancer element 6 kb upstream of the mouse HNF4α1 promoter is activated by glucocorticoids and liver-enriched transcription factors - Bailly, Alain (Oxford University Press, 2001)
We have characterized a 700 bp enhancer element around –6 kb relative to the HNF4α1 transcription start. This element increases activity and confers glucocorticoid induction to a heterologous as well as the homologous promoters in differentiated hepatoma cells and is transactivated by HNF4α1, HNF4α7, HNF1α and HNF1β in dedifferentiated hepatoma cells. A 240 bp sub-region conserves basal and hormone-induced enhancer activity. It contains HNF1, HNF4, HNF3 and C/EBP binding sites as shown by DNase I footprinting and electrophoretic mobility shift assays using nuclear extracts and/or recombinant HNF1α and HNF4α1. Mutation analyses showed that the HNF1 site is essential for HNF1α transactivation and is required for full basal enhancer activity, as is the C/EBP site. Glucocorticoid response element consensus sites which overlap the C/EBP, HNF4 and HNF3 sites are crucial for optimal hormonal induction. We present a model that accounts for weak expression of HNF4α1 in the embryonic liver and strong expression in the newborn/adult liver via the binding sites identified in the enhancer.